Efeito do decocto de Bauhinia forficata sobre parâmetros comportamentais e metabólicos em ratos tratados com haloperidol - Peroza, Luis Ricardo (2012)
Schizophrenia is a psychiatric disorder that affects 1% of world population and its pharmacologic treatment consists in the use of antipsychotics. It is known that chronic treatment with classical antipsychotics, such as haloperidol, can cause motors disturbers, among which stands out the tardive dyskinesia (TD). The TD pathophysiology has been associated with oxidative stress increase in areas of the brain related to the movements control. So, studies have proposed the use of natural compounds with antioxidants properties to decrease the production of reactive species on TD or on animals models of orofacial dyskinesia (OD). Bauhinia forficata (B. forficata), a plant used on folk medicine such as hypoglycemic, and presents antioxidant properties, could be used to reduce the oxidative stress present on OD. Thus, the first aim of this study was evaluate the effect of B. forficata on in vitro lipid peroxidation induced by pro-oxidants and also, the possible protector effect on OD, through of the quantifications of vacuous chewing movements (VCM), and on locomotor and exploratory activities decrease induced by haloperidol in rats (manuscript 1). B. forficata prevented the lipid peroxidation by pro-oxidant agents nitroprusside sodium, Fe2+/EDTA and Fe2+. Furthermore, adult male rats received haloperidol (38 mg/kg) each 28 days for 16 weeks and B. forficata decoction (2.5 g/L) on the place of drinking water or water to drink everyday for 16 weeks. The haloperidol treatment increased the VCM and reduced the locomotor and exploratory activities relative to control group on open field test. B. forficata co-treatment was not able to prevent the motor alterations induced by haloperidol, as well as only partially prevented VCM in rats. On the other hand, B. forficata caused an increase on locomotor activity. These results showed that B. forficata has antioxidant potential, but this effect is associated partially to protection against VCM induced by haloperidol in rats (manuscript 1). Some studies have showed that chronic treatment with classic antipsychotics can cause metabolic side effects. B. forficata which is known on folk medicine by glycemia decrease, could prevent the metabolic side effects caused by use of antipsychotics. So, the other propound of this study was to investigate the weight gain, glycemic levels and other metabolic parameters in rats chronically treated with haloperidol and the possible effect of B. forficata on these metabolic side effects (manuscript 2). After 16 weeks of treatment, the animals treated with haloperidol showed high glycemic prevalence and high glucose levels. B. forficata co-treatment elevated glucose and triglycerides levels. No difference was observed on cholesterol, urea, creatinine, alanine aminotransferase (AST), aspartate aminotransferase (ALT) and lactate dehydrogenase (LDH). Haloperidol treatment caused weight gain and promoted a significant decrease on brain/body weight rate. In conclusion, B. forficata co-treatment and haloperidol can increase the number of hyperglycemic animals. Thus, is necessary to emphasize the importance of more toxicology studies on chronic treatment with B. forficata to avoid health implications of population.